(untitled) (Comprehensive Journal of Science, 2026)
This study aims to explore the impact of banking integration and partnership on managing the geopolitical and systemic risks of electronic payment systems, applied to the Libyan banking environment, specifically focusing on (Jumhouria Bank and Sahara Bank). The research problem crystallizes in the "interdependency dilemma" and the near-total reliance on a centralized infrastructure (the National Switch), which creates a sovereign "single point of failure". This dependency makes the payment infrastructure highly vulnerable to political conflicts, institutional divisions, and geopolitical cyber threats. The study adopted a descriptive-analytical approach, utilizing a questionnaire to collect data from a purposive sample of 40 technical and administrative staff members at Jumhouria and Sahara banks. The results revealed a significant success in achieving technical integration with the National Switch; however, this progress was not matched by a similar level of security and sovereign integration. Furthermore, the findings proved that excessive centralized reliance, in the absence of decentralized contingency plans, creates severe vulnerability to geopolitical shocks. The study recommended the necessity of transitioning to "Zero Trust" models in APIs, establishing alternative and geographically distributed sovereign data centers, and founding a unified cyber operations room to enhance operational and sovereign resilience.